Evaluation of a targeted prescriber education intervention on emergency department discharge oxycodone prescribing. (24th May 2017) - Donaldson, Síne R; Harding, Andrew M; Taylor, Simone E; Vally, Hassan; Greene, Shaun L
Abstract: Objectives: The objective of this study was to evaluate the impact of an educational intervention on ED discharge opioid analgesic (OA) prescribing. Methods: A brief, one‐on‐one, educational intervention was delivered to ED OA prescribers by an ED clinical champion. The percentage of patients receiving (i) written advice regarding appropriate oxycodone use, (ii) written or verbal advice regarding appropriate post‐discharge follow up and (iii) written general practitioner notification that oxycodone had been prescribed were determined pre‐ and post‐intervention, through review of electronic patient records and structured patient telephone interviews conducted 3–7 days after ED attendance. Secondary outcomes included total amount prescribed and use of non‐OA therapies. ED OA prescribers were surveyed to evaluate perceived effectiveness and intervention acceptability. Results: A total of 30 ED OA prescribers received the 5‐min intervention. Pre‐ and post‐intervention, 80 and 81 patients were interviewed, respectively. Percentage of patients given written OA information increased from 10% to 22% ( P = 0.04) and those receiving follow‐up advice increased from 61 to 94% ( P < 0.01). General practitioner notification of OA prescription increased from 15% to 88% ( P < 0.01). Risk ratio for achieving all three end‐points was 7.5 (95% confidence interval 1.8–32, P = 0.01). Median total amount of oxycodone prescribed/patient decreased from 100mg to 50mg ( P = 0.04). Non‐OA therapies were used by 49% of pre‐intervention and 85% of post‐intervention patients ( P = <0.01). All ED OA prescribers agreed the intervention would change their prescribing practices; 70% deemed the intervention appropriate for delivery in their work environment. Conclusion: A brief, one‐on‐one educational intervention targeting ED OA prescribers was well received by clinicians and associated with improved quality of OA prescribing.